Overeating Behavior and Striatal Dopamine with 6-[18F]-Fluoro-L-𝑚-Tyrosine PET - Claire E. Wilcox; Meredith N. Braskie; Jennifer T. Kluth; William J. Jagust (Journal of Obesity)
Eating behavior may be affected by dopamine synthesis capacity. In this study, 6-[18F]-fluoro-L-𝑚-tyrosine (FMT) positron emission tomography (PET) uptake in striatal subregions was correlated with BMI (kg/m2) and an estimate of the frequency of prior weight loss attempts in 15 healthy subjects. BMI was negatively correlated with FMT uptake in the dorsal caudate. Although the association between BMI and FMT uptake in the dorsal caudate was not significant upon correction for age and sex, the association fell within the range of a statistical trend. Weight loss attempts divided by years trying was also negatively correlated with FMT uptake in the dorsal putamen (𝑃=.05). These results suggest an association between low dorsal striatal presynaptic dopamine synthesis capacity and overeating behavior.